2015
DOI: 10.1242/jeb.128959
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and melanic-specific variations in the oxidative status of adult tawny owls in response to manipulated reproductive effort

Abstract: Oxidative stress, determined by the balance between the production of damaging reactive oxygen species (ROS) and antioxidant defences, is hypothesized to play an important role in shaping the cost of reproduction and life history trade-offs. To test this hypothesis, we manipulated reproductive effort in 94 breeding pairs of tawny owls (Strix aluco) to investigate the sex-and melanism-specific effects on markers of oxidative stress in red blood cells (RBCs). This colour polymorphic bird species shows sex-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
1
10
1
Order By: Relevance
“…It has been shown that dark eumelanic and light pheomelanic individuals signal their abilities to cope with oxidative stress differently along environmental gradients so that eumelanic individuals would cope better under stressful conditions (large brood size) than pheomelanic individuals (e.g. Emaresi et al, 2016). Our results, however, showed a different pattern.…”
Section: Euemelanic and Pheomelanic Phenotypes In Stressful Conditionscontrasting
confidence: 64%
“…It has been shown that dark eumelanic and light pheomelanic individuals signal their abilities to cope with oxidative stress differently along environmental gradients so that eumelanic individuals would cope better under stressful conditions (large brood size) than pheomelanic individuals (e.g. Emaresi et al, 2016). Our results, however, showed a different pattern.…”
Section: Euemelanic and Pheomelanic Phenotypes In Stressful Conditionscontrasting
confidence: 64%
“…The following exclusion criteria were applied: i) studies that measured expression of antioxidant genes because I were interested in the biochemical differences between sexes; ii) studies that used metrics of free radical generation as an index of oxidative stress, since they do not provide direct evidence of oxidative stress (reactive species might be mopped up before oxidative damage is generated); iii) studies where necessary information for calculating effect size was unavailable. Overall, the final dataset included 732 effect sizes from 100 articles (82 species: 7 fish, 5 reptiles, 44 birds, and 26 mammals) (Almroth et al 2008; Alonso-Alvarez et al 2004a, 2004b; Barrera-GarcĂ­a et al 2012; Beamonte-Barrientos and Verhulst 2013; Beaulieu and Schaefer 2014, Beaulieu et al 2010, 2011, 2014; Bertrand et al 2006; Bilham et al 2013; Bize et al 2008; Bonisoli-Alquati et al 2010; Canovas et al 2014; Casagrande et al 2011, 2012a, 2012b; Cecere et al 2016; Christensen et al 2015; Christie et al 2012; Cohen et al 2008; Costantini and Bonadonna 2010; Costantini and Dell’omo 2015; Costantini et al 2007, 2008, 2010, 2012a, 2012b, 2013, 2014, 2014a, 2014b; Costantini 2010; Cram et al 2015a, 2015b; Depboylu et al 2013; Ehrenbrink et al 2006; Emaresi et al 2016; Figueiredo-Fernandes et al 2006b; Georgiev et al 2015; Gomes et al 2014; Grunst et al 2014; Heiss and Schoech 2012; Herrera-Dueñnas et al 2014; Isaksson et al 2009, 2011, 2013; Isaksson 2013; Jolly et al 2012; Kamper et al 2009; Kanerva et al 2012; Kayali et al 2007; Kurhalyuk et al 2009; Langley-Evans and Sculley 2005; Leclaire et al 2015; Lilley et al 2014; Lopes...…”
Section: Methodsmentioning
confidence: 99%
“…These blood-diluted samples were stored on ice in the dark for a maximum of 10 h prior to laboratory analysis. In the tawny owl (Strix aluco), we found no evidence that RBC membrane resistance and ROS production were explained by the time elapsed between sampling in the field and analyses in the laboratory (mean time elapsed in hours ± standard deviation = 10:37 ± 06:20, range = 02:00-22:15; n = 325 and 271 samples for RBC membrane resistance and ROS production; all P values >0.20; Emaresi et al 2016).…”
Section: Blood Samplingmentioning
confidence: 58%